Complementary Therapy In Overcoming Depression Schizophrenia Patients - I Wayan Septa Wijaya; I Gede Putu Oka; Satriya Pranata; Fatkhul Mubin (Yayasan Lentera Mitra Lestari, 2026)
Background: Schizophrenia is a mental health condition that places a significant burden on those affected. It typically emerges during adolescence or early adulthood and is often marked by recurrent positive symptoms. When depressive symptoms are present in individuals with schizophrenia, these individuals often struggle to fulfill their roles within their families and society effectively. Treatment options include both pharmacological and non-pharmacological strategies. Non-pharmacological interventions can be delivered through complementary therapies. Aims: This literature review aims to identify such therapies that can help alleviate depression in patients with schizophrenia. Method: In the process article search via PubMed and Science Direct using the keyword